2012
DOI: 10.1038/cdd.2011.198
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of Bim and Erk-mediated BimEL phosphorylation are dispensable for hematopoietic homeostasis in vivo

Abstract: The pro-apoptotic BH3-only protein Bim has a major role in hematopoietic homeostasis, particularly in the lymphocyte compartment, where it strongly affects immune function. The three major Bim isoforms (Bim EL , Bim L and Bim S ) are generated by alternative splicing. Bim EL , the most abundant isoform, contains a unique sequence that has been reported to be the target of phosphorylation by several MAP kinases. In particular, Erk1/2 has been shown to interact with Bim EL through the DEF2 domain of Bim EL and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…1, A and B). Of the three major BIM isoforms (BIM(EL), BIM(L), and BIM(S)) that are generated by alternative splicing, Bim(EL) is the most abundant and contains a unique sequence that has been reported to be the target of phosphorylation by several MAP kinases (26). BIM and BIK induction by GDC-0623 was also observed in KRAS mutant SW620 cells (Fig.…”
Section: Methodsmentioning
confidence: 85%
“…1, A and B). Of the three major BIM isoforms (BIM(EL), BIM(L), and BIM(S)) that are generated by alternative splicing, Bim(EL) is the most abundant and contains a unique sequence that has been reported to be the target of phosphorylation by several MAP kinases (26). BIM and BIK induction by GDC-0623 was also observed in KRAS mutant SW620 cells (Fig.…”
Section: Methodsmentioning
confidence: 85%
“…[56][57][58][59][60] However, a recent study has shown that ERK-mediated direct phosphorylation of BIM does not have a major role in the control of the proapoptotic activity of this BH3-only protein within the whole animal. 61 Both BIM and BMF were shown to be sequestered by binding to elements of the cytoskeleton, thereby restraining their pro-apoptotic activity. 62,63 Interestingly, loss of the transcription factor ASCIZ, with consequent reduction in its target dynein light chain 1, which reportedly links BIM to the dynein motor complex, 62 causes abnormal death of B lymphoid cells, and this can be blocked by concomitant loss of BIM.…”
Section: The Bcl-2-regulated Apoptotic Pathwaymentioning
confidence: 99%
“…The significance of this degradation for hematopoietic homeostasis has, however, recently been questioned. 19 The second reported Bim phosphorylation occurs in response to UV radiation or the negative selection of thymocytes, 20,21 and perhaps also in response to TRAIL 22 and involves the c-Jun N-terminal kinases 1 and 2 (JNK1/2)-mediated phosphorylation of Bim EL at T112 and Bim L at T56. This phosphorylation appears to release Bim from DLC1 21 and to increase its binding affinities to Bcl-2-like survival factors, 20 therefore endowing it with an increased apoptotic potential to activate Bax and Bak, and MOMP.…”
mentioning
confidence: 99%